Evidence for perchlorates and the origin of chlorinated hydrocarbons detected by SAM at the Rocknest aeolian deposit in Gale Crater. Issue 10 (1st October 2013) - Glavin, Daniel P.; Freissinet, Caroline; Miller, Kristen E.; Eigenbrode, Jennifer L.; Brunner, Anna E.; Buch, Arnaud; Sutter, Brad; Archer, P. Douglas; Atreya, Sushil K.; Brinckerhoff, William B.; Cabane, Michel; Coll, Patrice; et al.
<x xml:space="preserve">Abstract</x> [1] A single scoop of the Rocknest aeolian deposit was sieved (< 150 µm), and four separate sample portions, each with a mass of 50 mg, were delivered to individual cups inside the Sample Analysis at Mars (SAM) instrument by the Mars Science Laboratory rover's sample acquisition system. The samples were analyzed separately by the SAM pyrolysis evolved gas and gas chromatograph mass spectrometer analysis modes. Several chlorinated hydrocarbons including chloromethane, dichloromethane, trichloromethane, a chloromethylpropene, and chlorobenzene were identified by SAM above background levels with abundances of 0.01 to 2.3 nmol. The evolution of the chloromethanes observed during pyrolysis is coincident with the increase in O2 released from the Rocknest sample and the decomposition of a product of N‐methyl‐N‐(tert‐butyldimethylsilyl)‐trifluoroacetamide (MTBSTFA), a chemical whose vapors were released from a derivatization cup inside SAM. The best candidate for the oxychlorine compounds in Rocknest is a hydrated calcium perchlorate (Ca(ClO4)2·nH2O), based on the temperature release of O2 that correlates with the release of the chlorinated hydrocarbons measured by SAM, although other chlorine‐bearing phases are being considered. Laboratory analog experiments suggest that the reaction of Martian chlorine from perchlorate decomposition with terrestrial organic carbon from MTBSTFA during pyrolysis can explain the presence of three chloromethanes and a chloromethylpropene detected by SAM. Chlorobenzene may be attributed to reactions of Martian chlorine released during pyrolysis with terrestrial benzene or toluene derived from 2, 6‐diphenylphenylene oxide (Tenax) on the SAM hydrocarbon trap. At this time we do not have definitive evidence to support a nonterrestrial carbon source for these chlorinated hydrocarbons, nor do we exclude the possibility that future SAM analyses will reveal the presence of organic compounds native to the Martian regolith.